Human respiratory organoids sustained reproducible propagation of human rhinovirus C and elucidation of virus-host interaction - Cun Li; Yifei Yu; Zhixin Wan; Man Chun Chiu; Jingjing Huang; Shuxin Zhang; Xiaoxin Zhu; Qiaoshuai Lan; Yanlin Deng; Ying Zhou; Wei Xue; Ming Yue; et al. (Nature Communications)
Abstract The lack of a robust system to reproducibly propagate HRV-C, a family of viruses refractory to cultivation in standard cell lines, has substantially hindered our understanding of this common respiratory pathogen. We sought to develop an organoid-based system to reproducibly propagate HRV-C, and characterize virus-host interaction using respiratory organoids. We demonstrate that airway organoids sustain serial virus passage with the aid of CYT387-mediated immunosuppression, whereas nasal organoids that more closely simulate the upper airway achieve this without any intervention. Nasal organoids are more susceptible to HRV-C than airway organoids. Intriguingly, upon HRV-C infection, we observe an innate immune response that is stronger in airway organoids than in nasal organoids, which is reproduced in a Poly(I:C) stimulation assay. Treatment with α-CDHR3 and antivirals significantly reduces HRV-C viral growth in airway and nasal organoids. Additionally, an organoid-based immunofluorescence assay is established to titrate HRV-C infectious particles. Collectively, we develop an organoid-based system to reproducibly propagate the poorly cultivable HRV-C, followed by a comprehensive characterization of HRV-C infection and innate immunity in physiologically active respiratory organoids. The organoid-based HRV-C infection model can be extended for developing antiviral strategies. More importantly, our study has opened an avenue for propagating and studying other uncultivable human and animal viruses.